Impact of surgical approach for left ventricular assist device implantation on postoperative invasive hemodynamics and right ventricular failure. Issue 10 (16th July 2022) - Bjelic, Milica; Vidula, Himabindu; Wu, Isaac Y.; McNitt, Scott; Barrus, Bryan; Cheyne, Christina; Chase, Karin; Zottola, Zachary; Alexis, Jeffrey D.; Goldenberg, Ilan; Gosev, Igor
Abstract: Background: Right ventricular failure (RVF) remains one of the major causes of morbidity and mortality after left ventricular assist device (LVAD) implantation. We sought to compare immediate postoperative invasive hemodynamics and the risk of RVF following two different surgical approaches: less invasive surgery (LIS) versus full sternotomy (FS). Methods: The study population comprised all 231 patients who underwent implantation of a HeartMate 3 (Abbott) LVAD at our institution from 2015 to 2020, utilizing an LIS ( n = 161; 70%) versus FS ( n = 70; 30%) surgical approach. Outcomes included postoperative invasive hemodynamic parameters, vasoactive‐inotropic score (VIS), RVF during index hospitalization, and 6‐month mortality. Results: Baseline clinical characteristics of the two groups were similar. Multivariate analysis showed that LIS, compared with FS, was associated with the improved cardiac index (CI) at the sixth postoperative hour ( p = .036) and similar CI at 24 h, maintained by lower VIS at both timepoints ( p = .002). The LIS versus FS approach was also associated with a three‐fold lower incidence of in‐hospital severe RVF (8.7% vs. 28.6%, p < .001) and need for RVAD support (5.0% vs. 17.1%, p = .003), and with 68% reduction in the risk of 6‐month mortality after LVAD implantation (Hazard ratio, 0.32; CI, 0.13–0.78; p = .012). Conclusion: Our findings suggest that LIS, compared with FS, is associated with a more favorable hemodynamic profile, as indicated by similar hemodynamic parameters maintained by lower vasoactive‐inotropic support during the acute postoperative period. These findings were followed by a reduction in the risk of severe RVF and 6‐month mortality in the LIS group.